Validation of compressive test of biodegradable lumbar interbody spinal cage with different porous structure using computed tomography-based finite element analysis - Muhammad Hilmi, Jalil; M.H., Mazlan; Todo, Mitsugu (Springer Science and Business Media Deutschland GmbH, 2022)
Evaluation of spinal cage structures had been done using Computed tomographybased finite element analysis (CT/FEA) with homogenous bone properties. However, it is important to consider the inhomogeneity of bone properties in order to obtain more precise validation. This study compares the experimental and numerical analysis of CT/FEA by establishing relation between the Hounsfield Unit (HU) values, bone density and material properties. 6 cage designs with different pore structure were created and optimized based on the conventional bullet-shaped tip cage design. Specimens were fabricated using a fused deposition method (FDM) 3D printer. Unidirectional compression test machine was done and evaluated using FEA tool. A conventional bilateral mode configuration was applied to simulate standard PLIF procedure in the L4–L5. CT/FEA was done to characterize the stress profile of cage-endplate interface, cage body and failed element distribution. From the results, layers deviation and severe micro crack were seen at ruptured spinal cage specimen’s side surface. OPEN SOLID showed highest value of compressive value in the experiment and simulation. Finally, FEM stress profiles indicated that subsidence might have occurred for CLOSE 1 mm, OPEN SOLID, and OPEN 1 mm cage designs at the cage-endplate interface due to the sudden spike at endplate region. Overall, optimally designed PLA spinal cages have sufficient mechanical properties to support lumbar interbody loads. Furthermore, this optimization technique may be utilized to balance the complex requirements of load-transfer, stress shielding, and porosity when using biodegradable material for fusion spinal cages.